Mechanisms of Aortic Flow Deceleration and the Effect of Wave Reflection on Left Ventricular Function - Park, Chloe M.; Hughes, Alun D.; Henein, Michael Y.; Khir, Ashraf W. (Frontiers in Physiology, 2020)
Increased wave reflection is an independent predictor of cardiovascular events, possibly due to effects on left ventricular (LV) function. We investigated the relationship between reflected waves in early systole, the forward decompression wave in mid-late systole and LV mechanical behaviour. Invasively acquired ascending aortic velocity, pressure and LV long and minor axes’ dimensions were measured simultaneously in 11 anaesthetised dogs during both control conditions and aortic occlusion to cause additional early wave reflection. Wave intensity analysis was used to identify the arrival of the reflected wave and the onset of a forward expansion wave in mid-late systole. The arrival time of the reflected wave coincided with the time when minor axis shortening began to decline from its peak, even during aortic occlusion when this time is 12ms earlier. The initial decline in long axis shortening corresponded to the time of the peak of the reflected wave. The forward decompression wave was consistently observed to have a slow and then rapid phase. The slow phase onset coincided with time of maximum shortening velocity of the long axis. The onset of the later larger rapid phase consistently coincided with an increased rate of deceleration of both axes during late systole. Forward decompression waves are generated by the LV when the long axis shortening velocity falls. Reflected wave arrival has a detrimental effect on LV function, particularly the minor axis. These observations lend support to suggestions that therapies directed toward reducing wave reflection may be of value in hypertension and cardiovascular disease.